2005
DOI: 10.4037/ajcc2005.14.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Use of Physical Restraints in Adult Critical Care: A Bicultural Study

Abstract: • Background Although controversial, physical restraints are commonly used in adult critical care units in the United States to prevent treatment interference and self-inflicted harm. Use of physical restraints in Norwegian hospitals is very limited. In the United States, an experimental design for research on use of restraints has not seemed feasible. However, international research provides an opportunity to compare and contrast practices.• Objectives To describe the relationship between patients’ characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 26 publications
3
92
0
4
Order By: Relevance
“…Variations in practice were found internationally (Benbenbishty et al, 2010;Martin & Mathisen, 2005)…”
Section: Practice Variationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Variations in practice were found internationally (Benbenbishty et al, 2010;Martin & Mathisen, 2005)…”
Section: Practice Variationsmentioning
confidence: 99%
“…Clinical acuity and the use of physical restraint were considered in one international study (Martin & Mathisen, 2005). The Nursing…”
Section: The Influence Of the Working Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many forms of physical restraints, including wrist, ankle, chest, and waist (Maccioli et al, 2003). Adult ICUs use physical restraints much more than other units (Martin & Marthisen 2005), because critically ill patients may experience confusion or agitation in ICUs (Bray et al, 2004). Furthermore, a critical care environment may increase patients' stress and agitation (Powers, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the adverse effects of physical restraints, including physical and psychological injuries (Morrison et al, 2000;Choi & Song, 2003;Bray et al, 2004;Cotter, 2005). The reported physical injuries include: hypertension, tachycardia, impaired circulation, nerve and skin injury, orthostatic hypotension, urinary and fecal incontinence, edema, pressure ulcers, strangulation, contractures, cardiac arrest, muscle atrophy, and death from asphyxia (Morrison et al, 2000;Cotter, 2005;Martin & Marthisen, 2005). Psychological consequences of restraints involve increased agitation (Eşer et al, 2007), feeling of anger and fear (Rotondi & Chelluri, 2002), and the risk of developing post-traumatic stress disorder (Jones et al, 2007).…”
Section: Introductionmentioning
confidence: 99%